Quality assurance and public health safety of milk and milk products-a review - Anand, Sanjeev K (The Indian Journal of Animal Sciences, 2005)
Dairy sector is fast expanding not only in terms of volumes but also in adoption of new technologies. There is a boom of 'new era products' and modern technologies for extended shelf life products with lots of value addition. All this development has also opened avenues for the export of dairy products from the country, especially in the wake of increased opportunities in the post-WTO scenario. However, this has also posed a big challenge of producing safe and quality products. There have been concerns on the chemical and microbiological quality and safety aspects of milk and milk products that have been documented through various articles. The requirements with regard to the implementation of quality and food safety management systems have never been realized so urgently. The new concepts in milk production and processing, and the new product ideas such as genetically modified foods and the nutraceuticals have set new goals for quality assurance and food safety. This has also necessitated the greater emphasis on regulatory aspects with advanced methods of analysis and monitoring. With the strong research and developlnent support to the vibrant dairy industry, India is already emerging as a world leader in not only milk production, but also in the production of quality and safe milk and milk products for both domestic and global markets.